2011
DOI: 10.1038/eye.2011.279
|View full text |Cite
|
Sign up to set email alerts
|

The willingness of patients presenting with advanced glaucoma to participate in a trial comparing primary medical vs primary surgical treatment

Abstract: Aim The aim of this study is to examine the attitudes of patients, who presented with advanced glaucoma in at least one eye, to participation in a randomised prospective trial comparing primary medical treatment with primary surgical treatment for advanced glaucoma. Methods Patients who had presented with advanced glaucoma (415 dB loss mean deviation on Humphrey visual field testing) in at least one eye were asked to participate. Five focus groups comprising of 4-8 patients and consisting of 29 patients in tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…Descriptive statistics were used to compare demographic characteristics by group (healthy and glaucoma subjects). χ 3 tests were used to compare categorical variables, and t -tests were used to compare continuous variables. Mixed effects models were used to calculate the mean rates of change (slopes) for global cpRNFL thickness, global MRW thickness, and global macular GCIPL thickness loss from baseline.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Descriptive statistics were used to compare demographic characteristics by group (healthy and glaucoma subjects). χ 3 tests were used to compare categorical variables, and t -tests were used to compare continuous variables. Mixed effects models were used to calculate the mean rates of change (slopes) for global cpRNFL thickness, global MRW thickness, and global macular GCIPL thickness loss from baseline.…”
Section: Methodsmentioning
confidence: 99%
“…An estimated 10% to 39% of patients present with advanced glaucoma (OAG), and many are asymptomatic at the time of diagnosis. 1 3 Moreover, as the population ages and life expectancy increases, a larger proportion of patients will develop advanced disease. Advanced-OAG patients are, however, at the highest risk of becoming functionally impaired due to the disease and are the costliest to treat.…”
mentioning
confidence: 99%
“…As we hypothesized, patients were less likely to enroll in studies that compared an operative to a non-operative intervention than studies that compared two or more operative interventions, regardless of the country in which the trial was performed. This may be because patients have strong preferences surrounding the irrevocable nature of the decision to undergo surgery and are reluctant to leave this decision to chance [1] , [9] . Alternatively, patients may have a strong preference to undergo a surgical procedure that is the standard of care.…”
Section: Discussionmentioning
confidence: 99%
“…As suggested by several recent trials that have helped shape treatment recommendations for common orthopedic procedures, RCTs are pivotal for investigating the efficacy of surgical procedures or their components [5] , [6] , [7] . It may be challenging to enroll subjects into RCTs that randomly allocate subjects to different types of procedures, since surgery is irrevocable [8] , [9] . Previous studies have identified a number of reasons why an eligible individual may decline to participate in an RCT, such as a preference for one form of therapy over another, difficulty understanding the concept of an RCT, or discomfort with the idea of being randomized [1] , [10] , [11] , [12] , [13] .…”
Section: Introductionmentioning
confidence: 99%
“…Primary open-angle glaucoma (POAG) is a common clinical eye disease that is irreversible and causes blindness; it is a type of optic neuropathy characterized by the loss of retinal ganglion cells and their axons [1]. An estimated 10% to 39% of patients with POAG present with advanced glaucoma, and many are asymptomatic at the time of diagnosis [2][3][4].…”
Section: Introductionmentioning
confidence: 99%